The Correlation between Periodontal Diseases and Chronological Age among Type 2 Diabetes Mellitus Patients attending at National Healthcare Network (NHN) Mirpur Centre, Dhaka, Bangladesh (BIRDEM Medical Journal, 2013)
Background: The relationship between diabetes and periodontal diseases has been studied extensively during the past 50 years. Type 2 diabetes occurs mainly in people aged over 40, although it is affecting a growing number of young people. Patients with uncontrolled diabetes have poor resistance to infection with effects in mouth cavity and elsewhere in the body and show an unusually high susceptibility to periodontal diseases and increased susceptibility to acute lateral periodontal abscesses. Objective: This descriptive type of cross-sectional study was conducted to find out the relationship between periodontal diseases and chronological age among type 2 diabetes mellitus patients attending at National Healthcare Network (NHN) Mirpur Centre, Dhaka. Materials and Methods: A total 120 type 2 diabetic patients attended at diabetic centre for routine checkup over a period of six months from August 2011 to January 2012 who fulfilled the eligibility criteria were selected consecutively. Pre-tested semi structured interviewer administered questionnaires were used to collect the information. Cross tabulations and associations were determined by using the chi-square test and simple linear regression from Statistical Package for the Social Sciences where applicable. Results: Chronological age of the patients was significantly associated with the manifestation of periodontal diseases (p=0.004). Moreover, age was useful as a predictor of periodontal diseases as the correlation coefficients showed statistically significant result (p=0.008). In addition, for each year increase of age of the patients there was 0.20% increase of occurrence of periodontal diseases. Conclusion: Periodontal diseases can adversely affect the metabolic control of diabetes. Conversely, treatment of periodontal disease and reduction of oral inflammation may have a positive effect on the diabetic condition, although evidence for this remains somewhat equivocal. Birdem Med J 2013; 3(2): 74-79 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17209